3365 Treatment Interruptions and Early Discontinuation of Hormone Therapy in Hormone Receptor-Positive Breast Cancer Patients. (27th March 2019) - Mao, Daqin; Chang, Hong; Rodday, Angie Mae; Hachem, Hilal; Erban, John K.; Freund, Karen; Parsons, Susan
Abstract : OBJECTIVES/SPECIFIC AIMS: (1) To evaluate the association of patient and clinical factors with adherence to adjuvant hormone therapy (HT). (2) To examine the association of HT-related symptoms and the extent of remediation with early discontinuation of hormone therapy. METHODS/STUDY POPULATION: Retrospective cohort study of risk factors for interruption and early discontinuation of adjuvant hormone therapy in hormone receptor-positive nonmetastatic breast cancer patients diagnosed between 2009 and 2015. This study will include incident hormone receptor-positive breast cancer patients who initiated their HT and were followed at Tufts MC until Dec 31, 2016. Primary data source is electronic medical records (EMRs) RESULTS/ANTICIPATED RESULTS: The primary outcome of this study is early discontinuation to HT, defined as the first treatment gap of greater than or equal to 180 days following the initiation of HT. Treatment interruption, defined as any patient- or provider-initiated treatment gap of ≥ 2 weeks, will be examined as the secondary endpoint. Any HT-related symptoms occurred during a follow-up interval will be captured and categorized into five major types (i.e., vasomotor, neuropsychological, gastrointestinal, gynecological, and musculoskeletal symptoms). Onset and duration of a HT-related symptom will be recorded. Severity of the symptoms will also be rated by clinical oncologists. Remediations in response to HT- related symptoms will be collected and categorized into to two groups (pharmacological or non-pharmacological) and whether they were patient- or provider-initiated. Response to a remediation is defined as complete relief, partial relied, no relief, or with worsening symptoms. Response to a treatment change (i.e., HT switch or hold) was collected separately but using the same criteria. Analyses will be performed on the association between patient and clinical factors with rates of nonadherence (unplanned treatment interruption and/or early discontinuation) of hormone therapy, respectively. We also will explore whether patients with elevated symptoms and/or incomplete remediation will have earlier discontinuation of hormone therapy. DISCUSSION/SIGNIFICANCE OF IMPACT: Through formal chart review, we will establish a dataset that contains highly detailed information about treatment-emergent symptoms and remediations, which will enable us to quantitatively assess the impact of these treatment factors on adherence to hormone therapy for breast cancer. The in-depth analysis of risk factors associated with nonadherence to hormone therapy will inform development of interventions to improve cancer outcomes.